2008
DOI: 10.1128/mcb.00048-08
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions of POT1 at Telomeres

Abstract: The mammalian protein POT1 binds to telomeric single-stranded DNA (ssDNA), protecting chromosome ends from being detected as sites of DNA damage. POT1 is composed of an N-terminal ssDNA-binding domain and a C-terminal protein interaction domain. With regard to the latter, POT1 heterodimerizes with the protein TPP1 to foster binding to telomeric ssDNA in vitro and binds the telomeric double-stranded-DNA-binding protein TRF2. We sought to determine which of these functions-ssDNA, TPP1, or TRF2 binding-was requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 58 publications
(142 reference statements)
5
47
1
Order By: Relevance
“…19 Similar to mouse cells, knockdown of POT1 in human cells also resulted in accumulation of RPA at telomeres. 20,21 Together, these studies convincingly showed that, POT1, which binds to telomeric ssDNA in a sequence-specific manner, represses ATR activation in vivo by antagonizing the non-sequence-specific binding of RPA to telomeric ssDNA.…”
Section: Pot1 Is a Critical Repressor Of Atr Activation At Telomeresmentioning
confidence: 82%
See 2 more Smart Citations
“…19 Similar to mouse cells, knockdown of POT1 in human cells also resulted in accumulation of RPA at telomeres. 20,21 Together, these studies convincingly showed that, POT1, which binds to telomeric ssDNA in a sequence-specific manner, represses ATR activation in vivo by antagonizing the non-sequence-specific binding of RPA to telomeric ssDNA.…”
Section: Pot1 Is a Critical Repressor Of Atr Activation At Telomeresmentioning
confidence: 82%
“…3 Among these shelterin components, TRF1 and TRF2 interact with telomeric dsDNA in a sequence-specific manner, whereas POT1, in a complex with TPP1, binds to protection, 20,41,42 they are neither necessary nor sufficient for the localization of POT1 to telomeres. 8,20,43 Indeed, while a point mutation in the OB fold abolished POT1a binding to telomeric ssDNA in vitro, this mutant efficiently localized to telomeres in vivo. 10 These results suggest that POT1 needs to be recruited to telomeres by another mechanism to enable its direct binding to telomeric ssDNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere maintenance has been implicated in cancer and ageing, and requires cooperation between a multitude of telomeric factors, including telomerase, TRF1, TRF2, RAP1, TIN2, Tankyrase, PINX1 and POT1 (14)(15)(16). Among these proteins, TPP1 and POT1 directly bind single-stranded telomere DNA and interact with a number of proteins to maintain telomere length and structure (17)(18)(19). Therefore, the two proteins probably are the major players of telomere maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of human RPA in telomere maintenance Most human RPAs do not co-localize with telomerebinding protein TRF1 on the telomeres in IMR90 cells, suggesting that RPA is not a constitutive telomere binding protein. 41) However, Karlseder et al analyzed the telomere binding of RPA at various stages of the cell cycle in IMR90 by ChIP assay, and found that RPA binds to telomeres in the S phase and the G2 phase. 42) They proposed that RPA and other proteins involved in Lines represent telomereic DNA.…”
Section: )mentioning
confidence: 99%